Modern pedagogical education in the conditions of blended learning - Tatyana D. Shaposhnikova; Natalia N. Naydenova; Igor G. Sukhin; Ekaterina A. Vorontsova; Vladimir A. Myasnikov (Revista on line de Política e Gestão Educacional)
The present study is theoretical and aims to explore and critically evaluate the experience of blended learning demonstrated by countries that have attained a high level of education. Using a complex of theoretical methods, the study provides an analysis of the concept of blended learning, which combines both the traditional forms of education, the methods of distance learning, and innovative e-learning technologies. The models of blended learning found to be most successful in practical implementation are analyzed. The provided examples and recommendations for organizing blended learning in pedagogical education in foreign countries and a discussion of the challenges of its implementation and the possibilities of overcoming them can be useful in the use of blended learning in the Russian system of education, considering the domestic specifics. The study results suggest that the effectiveness of pedagogical education can be ensured by means of a combined implementation of different forms of e-learning and traditional learning – through blended learning.